2009
DOI: 10.1111/j.1600-0625.2008.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular calcium on the growth‐differentiation switch in immortalized keratinocyte HaCaT cells compared with normal human keratinocytes

Abstract: Abstract:The keratinocyte growth and differentiation switch, tightly regulated by several mechanisms, is generally associated with decreased proliferation, cell cycle arrest in G0 ⁄ G1 phase and expression of epidermal differentiation markers, such as keratin 1 (K1), keratin 10 (K10) and involucrin. In vitro, the spontaneously immortalized human keratinocyte cell line HaCaT is often used as a model to study keratinocyte functions. Comparative differentiation studies between HaCaT cells and normal human keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 45 publications
13
131
2
2
Order By: Relevance
“…Expression of KRT1 occurs mainly in the suprabasal layer and stratum spinosum in human epidermis (Yuspa et al, 1988). It has been reported that HaCaT cells differentiate in response to elevated Ca 2+ in a manner similar to normal epidermal keratinocytes, but HaCaT cells require somewhat higher extracellular Ca 2+ concentration and a longer time to launch the differentiation process (Micallef et al, 2009;Sakaguchi et al, 2003). As shown in Fig.…”
Section: +mentioning
confidence: 85%
See 2 more Smart Citations
“…Expression of KRT1 occurs mainly in the suprabasal layer and stratum spinosum in human epidermis (Yuspa et al, 1988). It has been reported that HaCaT cells differentiate in response to elevated Ca 2+ in a manner similar to normal epidermal keratinocytes, but HaCaT cells require somewhat higher extracellular Ca 2+ concentration and a longer time to launch the differentiation process (Micallef et al, 2009;Sakaguchi et al, 2003). As shown in Fig.…”
Section: +mentioning
confidence: 85%
“…cDNA synthesis was performed with Omniscript (Qiagen), using 0.5 mg total RNA, and quantitative RT-PCR was performed using the SYBR Green PCR Master Mix (Applied Biosystems) with the ABI Prism 7000 Instrument (Applied Biosystems), using specific oligonucleotides [human KRT1, forward 59-ATTTCTGAGCTGAATCGTGTGATC-39, reverse 59-CTTGGCATC-CTTGAGGGCATT-39 (Micallef et al, 2009); GAPDH, forward 59-GAAGG-TGAAGGTCGGAGTC-39, reverse 59-GAAGATGGTGATGGGATTTC-39].…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Because elevation of extracellular calcium modulates cellular properties in addition to cadherin-based-adhesion induction (43,44), we sought to isolate the role of cadherin in spatially organizing traction forces. We used two different methods to inhibit formation of cadherinbased adhesions in the presence of high-calcium medium.…”
Section: Cadherin-based Adhesions Are Required For Organization Of Trmentioning
confidence: 99%
“…Calcium signaling is a key element of keratinocyte differentiation [357][358][359][360] and, as we suggested above, altered differentiation of epidermal keratinocytes may play a role in pruritic diseases such as e.g. AD and psoriasis [361].…”
Section: Trpcs and Keratinocyte Differentiationmentioning
confidence: 99%